Novel 3,4-Dihydroisocoumarins Inhibit Human P-gp and BCRP in Multidrug Resistant Tumors and Demonstrate Substrate Inhibition of Yeast Pdr5 - Sachs, Julia; Döhl, Katja; Weber, Anja; Bonus, Michele; Ehlers, Ferdinand; Fleischer, Edmond; Klinger, Anette; Gohlke, Holger; Pietruszka, Jörg; Schmitt, Lutz; Teusch, Nicole (Frontiers in Pharmacology, 2019)
Multidrug resistance (MDR) in tumors and pathogens remains a major problem in the efficacious treatment of patients by reduction of therapy options and subsequent treatment failure. Various mechanisms are described to be involved in the development of MDR with overexpression of ATP-binding cassette (ABC) transporters reflecting the most extensively studied. These membrane transporters translocate a wide variety of substrates utilizing energy from ATP hydrolysis leading to decreased intracellular drug accumulation and impaired drug efficacy. One treatment strategy might be inhibition of transporter-mediated efflux by small molecules. Isocoumarins and 3,4-dihydroisocoumarins are a large group of natural products derived from various sources with great structural and functional variety, but have so far not been in the focus as potential MDR reversing agents. Thus, three natural products and nine novel 3,4-dihydroisocoumarins were designed and analyzed regarding cytotoxicity induction and inhibition of human ABC transporters P-glycoprotein (P-gp), multidrug resistance-associated protein 1 (MRP1) and breast cancer resistance protein (BCRP) in a variety of human cancer cell lines as well as the yeast ABC transporter Pdr5 in Saccharomyces cerevisiae. Dual inhibitors of P-gp and BCRP and inhibitors of Pdr5 were identified, and distinct structure-activity relationships for transporter inhibition were revealed. The strongest inhibitor of P-gp and BCRP, which inhibited the transporters up to 80% to 90% compared to the respective positive controls, demonstrated the ability to reverse chemotherapy resistance in resistant cancer cell lines up to 5.6-fold. In the case of Pdr5, inhibitors were identified that prevented substrate transport and/or ATPase activity with IC50 values in the low micromolar range. However, cell toxicity was not observed. Molecular docking of the test compounds to P-gp revealed that differences in inhibition capacity were based on different binding affinities to the transporter. Thus, these small molecules provide novel lead structures for further optimization.